Ginsenoside Rg1 Ameliorates Neuroinflammation via Suppression of Connexin43 Ubiquitination to Attenuate Depression - Huiqin Wang; Huiqin Wang; Yantao Yang; Songwei Yang; Siyu Ren; Juling Feng; Yangbo Liu; Haodong Chen; Naihong Chen; Naihong Chen (Frontiers in Pharmacology, 2021)
Depression is an inflammation-associated disease that results in major depression as inflammation increases and progresses. Ginsenoside Rg1 (Rg1), the major bioactive ingredient derived from ginseng, possesses remarkable anti-depressant and anti-inflammatory effects. Our previous studies showed that the pathogenesis of depression was concomitant with the acceleration of connexin43 (Cx43) ubiquitin degradation, while Rg1 could upregulate Cx43 expression to attenuate depression. However, whether the ubiquitination of Cx43 is the specific correlation between depression and inflammation, and how Rg1 ameliorates neuroinflammation to attenuate depression, are still under investigation. In in vivo experiments, Rg1 treatment significantly ameliorated depression-like behaviors in rats subjected to chronic unpredictable stress (CUS). Moreover, these CUS rats treated with Rg1 exhibited attenuated neuroinflammation, together with the suppression of Cx43 ubiquitination. In in vitro experiments, Rg1 reduced the secretion of inflammatory cytokines and the ubiquitination of Cx43 in lipopolysaccharide-induced glial cells. Furthermore, treatment with ubiquitin-proteasome inhibitor MG132 suppressing the ubiquitination of Cx43 ameliorated lipopolysaccharide-induced neuroinflammation. The results suggest that Rg1 attenuates depression-like behavioral performances in CUS-exposed rats; and the main mechanism of the antidepressant-like effects of Rg1 appears to involve protection against neuroinflammation via suppression of Cx43 ubiquitination. In conclusion, Rg1 could ameliorate neuroinflammation via suppression of Cx43 ubiquitination to attenuate depression, which represents the perspective of an innovative therapy of Rg1 in the treatment of inflammation-associated depression.